What About Mozart? What About Murder? Reasoning from Cases - MUNTANYOLA SAURA, Dafne (Revista Española de Investigaciones Sociológicas, 2024)
What about mozart? What about murder?: reasoning from cases Howard S. Becker The University of Chicago Press, 2014